Mathematical (Seirb) Model Analysis for Evaluating Cholera Control Strategies in Remote Dry Season Region - DERE, Zainab Olabisi; OLADAPO, Asimiyu Olalekan (JURNAL DIFERENSIAL, 2024)
Cholera, caused by the Vibrio cholerae bacterium, poses a significant public health threat in remote regions of Nigeria, especially during the dry season when access to treated water is limited. This research aims to develop a comprehensive model to understand the rapid spread of cholera in these areas and evaluate the efficacy of control policies, including educational programs, antibiotics, water treatment rates, and environmental cleanliness through resolving the Existence and Uniqueness of the model formulation, Positivity, and Boundedness, Basic Reproduction Number, i.e. the threshold of the disease dynamics. When the versatility of the disease spreads will die out with time and if, the persistence of the disease prevails over time. Local and Global stability analysis of the model was obtained, also the sensitivity analysis for the targeted parameters was analyzed. Additionally, the study incorporates numerical simulations utilizing the homotopy perturbation method to identify the specific impact of the control parameters are for in mitigating the spread of the Vibrio cholerae disease. The result obtained seeks to provide valuable insights into designing effective intervention strategies aforementioned to combat cholera outbreaks in resource-constrained regions, with a focus on improving water accessibility and implementation.